The Effect of Sulfur Salts on Concrete (American Journal of Engineering , Mechanics and Architecture (2993-2637), 2024)
It is anticipated that the constant need for concrete will rise as a result of the rapid advancements in global construction. Due to this need, a significant amount of cement must be produced, which could have negative ecological effects like raising atmospheric CO2 emissions. This prompted a number of researchers to look for cement substitutes, and sulfur salts -based concrete is one such substitute. The amount of cement needed to manufacture regular concrete is decreased because to this concrete composite In order to produce Ordinary Portland Cement (OPC) can be partially substituted with sulfur in sulfur salts -based concrete. It is a composite matrix of building materials composed primarily of sulfur and aggregates. In terms of exceptional durability resistance, low heat conductivity, little shrinkage, quick early strength rise, and improved adhesion, sulfur-modified concrete performs better than regular concrete. Due to the exceptional qualities indicated above, sulfur salts -based concrete can be used as a primary building material for offshore projects, underground utility networks, and dams. This study provides a thorough understanding of the possible uses of sulfur salts -based concrete in the modern construction industry by analyzing the sources, emissions from construction companies, and compositions of sulfur; describing the properties and processes of sulfur production; and highlighting relevant literature.